2015
DOI: 10.1353/csd.2015.0005
|View full text |Cite
|
Sign up to set email alerts
|

College Student Motivation to Lead in Relation to Basic Psychological Need Satisfaction and Leadership Self-Efficacy

Abstract: We investigated basic need satisfaction and leadership self-efficacy as psychological antecedents of college students’ motivation to lead (MTL), while controlling for individual differences by gender and academic class. Preliminary analyses revealed significant gender differences with males scoring higher than females on calculative MTL and classification differences with seniors scoring higher on affective-identity MTL compared to less advanced students in college. When these demographic differences were cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The analysis suggested that PE students with high levels of intrinsic motivation rated higher in the overall value of satisfaction, as well as in the factors linked to competence, autonomy, and relatedness, with no predictive evidence with the relatedness. These results are shown in line with several previous studies in which intrinsic motivation was positively predicted by the satisfaction of psychological needs [33,34]. In addition, these results support the postulates of SDT proposed by Deci and Ryan [35], where the satisfaction of psychological needs can result in the development of positive adaptive behaviors that result in the promotion of personal well-being.…”
Section: Discussionsupporting
confidence: 92%
“…The analysis suggested that PE students with high levels of intrinsic motivation rated higher in the overall value of satisfaction, as well as in the factors linked to competence, autonomy, and relatedness, with no predictive evidence with the relatedness. These results are shown in line with several previous studies in which intrinsic motivation was positively predicted by the satisfaction of psychological needs [33,34]. In addition, these results support the postulates of SDT proposed by Deci and Ryan [35], where the satisfaction of psychological needs can result in the development of positive adaptive behaviors that result in the promotion of personal well-being.…”
Section: Discussionsupporting
confidence: 92%
“…In context, this usually refers to stimulating student interest in a content course, or what is known as intrinsic motivation. Motivation to learn is a long-standing problem in society and many relevant studies have presented and discussed it (Cho, Harrist, Steele, & Murn, 2015;Ambassador, 2015;Pintrich, 2003). Learning motivation is basically divided into two, namely intrinsic motivation and extrinsic motivation.…”
Section: Learning Motivationmentioning
confidence: 99%
“…Or in other words, leadership educators must generate developmental experiences where leaders can be created (Sternberg, 2011). Thus, as Cho et al (2015) (Bronk & McLean, 2016). Nevertheless, just as one's leadership competency can change depending on the situation, developmental readiness is also context-specific (Avolio, & Hannah, 2009;Cho et al, 2015;Hannah, Avolio, Luthans, & Harms, 2008;Murphy & Johnson, 2011;Waldman, Galvin, & Walumbwa, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But, being motivated to lead is not enough. Cho, et al (2015) found that motivation also impacts a student's resolution, or intent, to take on leadership responsibilities. Thus, understanding a student's motivation and intent to lead may be an important part of understanding how to develop those who will accept leadership roles in the future (Waldman et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%